Scientific cultivation of water chestnut crop a boon for poor fishermen - Singh, I S; Thakur, A K; Prakash, Dhiraj (Indian Farming, 2018)
With the research of varietal development programme of waterchestnut, it was observed that the fishermen have started growing water chestnut crop scientifically in their ponds or unused chaur lands in association with foxnut and fishes. Fishermen are happy with the newly identified thornless germplasm of water chestnut, as it is easy in plucking the fruit from the plants, transportation and post-harvest processing. As a result of this, the fishermen are getting almost two-fold higher income in comparison to their previous activities. The highest benefit: cost ratio was recorded with Foxnut-water chestnut combination (1.79) followed by foxnut-fish combination in field system under integrated farming system model.